2019
DOI: 10.1037/spq0000275
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ self-report of school satisfaction: The interaction between disability and gender.

Abstract: School satisfaction is a critical indicator of well-being for every child and adolescent. Yet studies have rarely investigated whether school satisfaction varies depending upon participant characteristics and school-related social factors. Here we investigated whether disability and gender moderate adolescents' self-report of school satisfaction. We also explored the role of mediating variables such as teacher support, parent support, and relationships with peers (including friendships and also bullying). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
3
20
1
Order By: Relevance
“…Our hypothesis that adolescent girls with disabilities would self-report the lowest school satisfaction was supported. Similar to the findings of Arciuli et al (2019) who examined Year 8 students (13-14 years of age) within a large nationally representative Australian dataset, we found an interaction between disability and gender such that adolescent girls with disabilities aged 14 years who live in the United Kingdom reported significantly lower levels of school satisfaction than predicted by the additive effects of female gender and disability. In line with Vaz et al (2015) who examined school belonging in 12-year-olds in a separate, smaller Australian study, we found that 11-year-old girls with disabilities who live in the United Kingdom had relatively high school satisfaction.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our hypothesis that adolescent girls with disabilities would self-report the lowest school satisfaction was supported. Similar to the findings of Arciuli et al (2019) who examined Year 8 students (13-14 years of age) within a large nationally representative Australian dataset, we found an interaction between disability and gender such that adolescent girls with disabilities aged 14 years who live in the United Kingdom reported significantly lower levels of school satisfaction than predicted by the additive effects of female gender and disability. In line with Vaz et al (2015) who examined school belonging in 12-year-olds in a separate, smaller Australian study, we found that 11-year-old girls with disabilities who live in the United Kingdom had relatively high school satisfaction.…”
Section: Discussionsupporting
confidence: 80%
“…While that study did not explore the possible intersection of disability and gender, discussion relating to changing gender effects over time included both gender differences in extracurricular offerings and gender differences in sensitivity to the quality of studentteacher relations in the later years of high school. In fact, Arciuli et al (2019) found that the association between disability and lower self-reported school satisfaction was mediated by students' perceived levels of teacher support which, in turn, was moderated by student gender. Specifically, more concerns regarding perceived lack of teacher support were reported by girls with disabilities.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations